Evaluasi Dampak Kondisi Lahan Tergenang Terhadap Produksi Kelapa Sawit - Dimas Yudha Prasetio; Edi Wiraguna (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Oil palm (Elaeis guineensis Jacq) is a key strategic commodity in Indonesia, playing a vital role in national exports and supporting various industries, including food production and renewable energy. Harvesting is a critical phase in oil palm cultivation, and its outcomes are significantly influenced by agronomic practices and environmental conditions, such as waterlogging. This study aimed to compare oil palm yields between waterlogged and non-waterlogged fields and to assess the statistical significance of any differences observed. The research was conducted at Tanjung Buluh Estate, Division 3 of PT Socfin Indonesia, located in Teluk Mengkudu, North Sumatra. A Randomized Complete Block Design (RCBD) was employed, focusing on a single factor: land condition (waterlogged vs. non-waterlogged). Results showed that the average fresh fruit bunch (FFB) yield from non-waterlogged plots was 109.4 kg, notably higher than the 78.9 kg recorded in waterlogged areas. A T-test yielded a P-value of 0.0929, approaching the 10% significance threshold, suggesting that waterlogging can potentially reduce oil palm productivity.